2007
DOI: 10.1002/ijc.22431
|View full text |Cite
|
Sign up to set email alerts
|

Management of early breast cancer in the elderly

Abstract: Breast cancer is the most common malignancy in women with an age related increase in incidence ranging from 1 in 50 at age 50 to 1 in 10 at age 80. This is particularly significant in view of the changing demographics in the western population, characterised by an aging population and increased life expectancy. However in spite of favourable prognostic factors and less aggressive biological behaviour, elderly breast cancer patients receive less aggressive treatment when compared with their younger counterparts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…Older patients often receive less aggressive treatment than younger patients (Rao et al 2007), but a study of 118 women aged over 80 years with breast cancer showed that the women treated with letrozole had better progression-free survival than those treated with tamoxifen (progression was 5/64 and 24/54 respectively; Garimella et al 2006). In the BIG 1-98 trial, letrozole, compared with tamoxifen, significantly reduced the risk of recurrence by 21% in patients aged 65 years or older (HR 0.79;95% CI 0.64-0.97;PZ0.02;Thürlimann et al 2005), while in the ATAC trial, anastrozole reduced the risk of recurrence by only 7% in women aged 65 years and older (HR 0.93; 95% CI 0.80-1.08) when compared with tamoxifen (Arimidex package insert 2005).…”
Section: Efficacy and Safety Of Adjuvant Endocrine Therapy In Older Pmentioning
confidence: 99%
“…Older patients often receive less aggressive treatment than younger patients (Rao et al 2007), but a study of 118 women aged over 80 years with breast cancer showed that the women treated with letrozole had better progression-free survival than those treated with tamoxifen (progression was 5/64 and 24/54 respectively; Garimella et al 2006). In the BIG 1-98 trial, letrozole, compared with tamoxifen, significantly reduced the risk of recurrence by 21% in patients aged 65 years or older (HR 0.79;95% CI 0.64-0.97;PZ0.02;Thürlimann et al 2005), while in the ATAC trial, anastrozole reduced the risk of recurrence by only 7% in women aged 65 years and older (HR 0.93; 95% CI 0.80-1.08) when compared with tamoxifen (Arimidex package insert 2005).…”
Section: Efficacy and Safety Of Adjuvant Endocrine Therapy In Older Pmentioning
confidence: 99%
“…Although relatively little is known about possible differences in the biology of BC in older patients compared to younger patients, it has been reported that advanced age is associated with less aggressive tumor features (Tipples and Robinson, 2009;Tang et al, 2011;Thomas and Leonard, 2009;Wildiers, 2008;Rao et al, 2007;Thapa et al, 2013;Zhao et al, 2014). In addition, an understanding of the relationship between age and life expectancy is vital in making clinical decisions regarding treatment (Rao et al, 2007). The average future life expectancy of a 65-year-old woman is nearly 20 years and that of an 80-year-old woman is 9 years (Tang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The average future life expectancy of a 65-year-old woman is nearly 20 years and that of an 80-year-old woman is 9 years (Tang et al, 2011). Both reductions in life expectancy and an increased frequency of comorbid illnesses account for diversions in standard BC treatment algorithms in elderly patients (Rao et al, 2007;Wyld and Reed, 2007). Treatment-related morbidity plays a significant role in the application of curative treatment in elderly patients; older patients are more likely to prefer an improvement in their current quality of life rather than a potential increase in survival (Yellen et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Age is the greatest risk factor for the development of new cases of breast cancer, and the incidence increases with age: 1 in 50 by age 50, 1 in 14 by age 70 and 1 in 9 by age 85 (2). Approximately 50% of breast cancers occur in women of 65 years of age or older and 35% occur after the age of 70 (3).…”
Section: Introductionmentioning
confidence: 99%